Implementasi Pendidikan Kesehatan di Sekolah Dasar - Juniansyah; Tiara Elana (Jurnal Pendidikan Dasar Islam, 2023)
The purpose of this research is to describe health education not only in class, but as a collection of experiences anywhere and anytime as long as it can influence knowledge, attitudes and habits of primary school education targets. This research method uses descriptive qualitative. This data source uses primary sources, namely from book literature, journal studies, magazines, or websites that support research. This data analysis uses descriptive analysis. The results of this study indicate that the implementation of school health education is first through intracurricular, second co-curricular and third through extracurricular.